2016
DOI: 10.1016/j.expneurol.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The multiple sclerosis drug fingolimod (FTY720) stimulates neuronal gene expression, axonal growth and regeneration

Abstract: Fingolimod (FTY720) is a new generation oral treatment for multiple sclerosis (MS). So far, FTY720 was mainly considered to target trafficking of immune cells but not brain cells such as neurons. Herein, we analyzed FTY720's potential to directly alter neuronal function. In CNS neurons, we identified a FTY720 governed gene expression response. FTY720 upregulated immediate early genes (IEGs) encoding for neuronal activity associated transcription factors such as c-Fos, FosB, Egr1 and Egr2 and induced actin cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 88 publications
4
55
0
1
Order By: Relevance
“…Like numerous cell surface receptor agonists, FTY720P can lead to S1PR internalization, effectively modulating their protein level at the cell surface. However, FTY720 / FTY720P can exert a number of other effects including changes in neuronal gene expression [38], as demonstrated by a previous study on a rat AD model induced by single Aβ injection [55]. In our hands, the long-term presence of AβPP (V717I) has notably modified the cortical responses to the treatment with FTY720.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…Like numerous cell surface receptor agonists, FTY720P can lead to S1PR internalization, effectively modulating their protein level at the cell surface. However, FTY720 / FTY720P can exert a number of other effects including changes in neuronal gene expression [38], as demonstrated by a previous study on a rat AD model induced by single Aβ injection [55]. In our hands, the long-term presence of AβPP (V717I) has notably modified the cortical responses to the treatment with FTY720.…”
Section: Resultsmentioning
confidence: 48%
“…The complex interactions of sphingolipids with nuclear gene regulation suggest close links between these pathways, but detailed understanding is missing. The ability of the sphingosine mimetic drug FTY720/fingolimod to modulate gene expression in neurons and astrocytes [38,39] is probably due in large part to the links observed between S1P receptor signaling and the activities of crucial transcription factors including NF-κB, Yin-Yang-1, or Notch [71][72][73][74][75]. However, the inhibition of class I HDACs by FTY720 / FTY720P must also be considered a potential mechanism [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies demonstrated a neuroregenerative effect as well as a neuroprotective effect on synapses of murine MS models after fingolimod treatment . The drug elicits a neuronal gene response, modulating neurite growth, and axonal regeneration …”
Section: Discussionmentioning
confidence: 93%
“…For cortical tissue (Figure M), the ΔΔCt method was applied to provide the fold change of mRNA level as follows: 2 −(ΔCt TBI ipsi − ΔCt sham ipsi) . Primer sequences were reported earlier or can be provided upon request …”
Section: Methodsmentioning
confidence: 99%